أهمية تقليص مدة إنجاز المشاريع في تخفيض التكاليف غير المباشرة: دراسة حالة مشروع 20 مسكن بالأغواط - الهاشمي، بعاج (جامعة عاشور زيان الجلفة - كلية العلوم الاقتصادية والعلوم التجارية وعلوم التسيير, 2023)
تهدف هذه الدراسة إلى إبراز أهمية تحليل شبكات الأعمال على اختلاف أنواعها (CPM, PERT) كوسيلة فعالة في جدولة المشاريع، ومن أهم الطرق المتبعة في تسريع وتيرة انجاز المشاريع نجد تقنية تقليص مدة انجاز المشاريع Crashing لأن الوقت والتكلفة هما من أهم مؤشرات الأداء. تم تطبيق طريقة تقليص مدة الإنجاز في مؤسسة البناء (ETB BAADJ)، وذلك لمشروع بناء 130/20 وحدة سكنية بولاية الأغواط، وأظهرت النتائج أن الطريقة المقترحة فعالية في خفض مدة الإنجاز ( 78 أسبوع بعدما كانت مدة الإنجاز في الأول 100 أسبوع)، ضف إلى أن التكاليف ( غير المباشرة) بدورها قد انخفضت 7800000) دج بعدما كانت 10000000 دج)، في الأخير تم استخلاص أن تقنية تقليص مدة إنجاز المشاريع تعد منظوراً جديداً للمجدولين في حل مشكلات إدارة المشاريع. This study aims to highlight the importance of analysis of different business networks |(CPM, PERT) as an effective means of scheduling projects. One of the most important ways to accelerate the pace of project delivery is the technique of reducing the duration of project delivery Crashing because time and cost are the most important performance indicators. The method of reducing the duration of completion has been applied in the construction institution (ETB BAADJ), for a project to build 20/130 housing units in Laghouat State, results show that the proposed method is effective in reducing the duration of completion (78 weeks after the first 100 weeks' completion period) indirect costs, in turn, have decreased (7,800,000 DZD after 10,000,000 DZD), in the latter, it was concluded that the project duration reduction technique was a new perspective for schedulers in solving project management problems..
Keywords: إدارة المشاريع -- المشاريع التنموية -- التنمية العمرانية -- الوحدات السكنية